Level of kinaesthetic differentiation of movement amplitude in polish national team wrestlers in various training stages - Starosta, W.; Fostiak, D.; Zurek, P. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
Directly physical contact with an opponent, linked with a speed and precise movements, executed in various technical-tactical combinations, calls for a high level of movement coordination in wrestlers. Kinaesthetic differentiation are the very important part of the movement coordination, because sensations influence the high precision of movements. Only kinaesthetic differentiation relevant to individual and favourable technique, can help to learn an master technique. Thus, it is important to keep on verifying these sensations by a competitor with the aid of a coach and other people involved in training. PURPOSE: The of this study was to investigate the relation between the precision of re-producing of the given bending angle of a limb and training stage, as well as to determine which limb is dominant. METHOD: The test for measuring the ability of kinaesthetic differentiation of a movement amplitude has been used. There were two sets for measuring: a kinaesthesiometer linked with a set of goniometers and computer. 107 wrestlers of Polish National Team were subject to this examination. That group consisted of classic style younger juniors (cadets), juniors and seniors, and free style younger juniors. Measuring was carried out once during the preparation period of training. CONCLUSIONS: 1. The precision of movement amplitude reproduction varied depending on training stage. The highest precision was recorded in seniors, and the lowest in classic style juniors. 2. Some statistically insignificant differentiation of the results for both upper limbs were observed. Left hand was more precise. 3. The highest symmetry of movements precision was observed in classic style younger juniors. 4. The results seem to confirm the versatile technical preparation of the wrestlers, i.e. symmetrical performing of exercises may result in better sport results in competition.